If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y = 12x + -16 Reorder the terms: 4y = -16 + 12x Solving 4y = -16 + 12x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '4'. y = -4 + 3x Simplifying y = -4 + 3x
| a^2/4/5-4/a | | 8j+3j-9j-1=13 | | 3p+5k=14 | | a/8-4/a^2/4 | | abs(x-12)=10 | | 8(2T+1)=(7T+7) | | 3(x-4)=6.9 | | 2/3/2-4/3 | | lx-12l=10 | | 4-1(6-9)= | | 2.3a-5=1.8a | | -20u+-3u-46u-33=-13 | | D-4=x | | -2(4y-1)+7y=4-y | | -11(-3)= | | 2/3x^2+12x+8/2x | | 9(-5)= | | 32(x+6)=-2(x-4) | | (1/3)^-2 | | 5a+25=100 | | -30/(-5) | | 4c=5c+18 | | -30/5 | | -11+4c=7+5c | | -30/-5 | | 0=3x^2+6-2 | | 35x-35/25x-40 | | 6z+12=5z+12 | | n/3+1=4 | | -3y-2=3-2y | | 2x/5-2=x/4+4 | | 5z-6=z+6 |